Competencies of Head Teachers and SMC Chairpersons in Financial Management in Elementary Schools: A Case Study - Hota, Swarna Prava; Panda, Gitanjali (THE PRIMARY TEACHER, 2022)
Head Teachers and the School Management Committee (SMC) are the main stakeholders entrusted with administrative roles in elementary schools to meet the financial objectives in Odisha. The dynamic changes in educational culture demand more knowledge, skills, values, and attitudes to achieve efficiency in financial management among the Principals and SMC members. The survey, with a well-structured questionnaire, was conducted in 58 government elementary schools across 116 respondents consisting of 58 head teachers and 58 SMC chairpersons. The objective of this study was to evaluate the competencies of primary schools in generating income and its effective utilisation for the school’s development through the perceptions of the two major stakeholder groups. Frequencies, percentages, and averages were used in descriptive statistics, whereas inferential statistics were used for hypothesis testing. At a significance level of 0.05 in the t-test, the study indicated that there is no significant difference between the mean ratings of Head Teachers and SMC Chairpersons in the case of financial management practices. The major issues relating to the financial management of schools are found to be poor knowledge regarding sources of funds and means of acquiring them, poor follow-up and tracking of budget preparation and evaluation, a lack of auditing abilities, and a lack of transparency in financial operations, which are crucial for managing finances. Therefore, the quality of education can be improved through efficient financial management by addressing these issues.